The current status and factors related to the preparation of home first-aid kits in China - Ge, Pu; Zhang, Jinzi; Lyu, Ke; Niu, Yuyao; Li, Qiyu; Xiong, Ping; Liu, Jiaxin; Yang, Yajie; Deng, Yuqian; Li, Xialei; Yu, Wenli; Yin, Mei; et al. (Frontiers in Public Health, 2022)
Background: Home first-aid kits can play an important role when residents are injured, suddenly become seriously ill or suffer from disasters. Purpose: To explore the home first-aid kit preparedness of Chinese residents and the relationship between demographic sociological characteristics, self-efficacy, Big Five personality, health literacy and home first-aid kit preparation behavior. Methods: A cross-sectional study was conducted. Information was collected through a self-designed questionnaire consisting of sociological characteristics, the New General Self-Efficacy Scale (NGSES), the Health Literacy Scale Short-Form (HLS-SF12), and the 10-item short version of Big Five Inventory (BFI-10). Rank sum test, Chi-square test, and logistic regression were used to explore the relationship between independent variables and home first-aid kit preparation behavior. Results: A total of 9,344 respondents were included, and 2,156 (23.07%) prepared home first-aid kits. Among the respondents who had prepared their home first-aid kits, disinfection supplies (85.20%), medical masks (84.51%), commonly used drugs (82.79%) were the most frequently available. The respondents whose geographic area was Central and Western China, permanent residence in the urban area, secondary education or above, monthly income of 3000 RMB or above, health care cost-bearing method mainly resident health insurance, high subgroup of self-efficacy, high subgroup of health care dimension in health literacy, and whose openness and conscientiousness was high subgroup were more likely to prepare home first-aid kits (P < 0.05). Conclusion: The preparation rate for home first-aid kits in China is less than a quarter. The public's home first-aid kit preparation behavior is related to demographic characteristics, self-efficacy, health literacy, and the openness of the Big Five personality. A multi-level linked national emergency literacy education system should be established to enhance the residents’ attention to home first-aid kits and improve the residents’ ability to prevent emergencies.